2011
DOI: 10.1177/0021998311401073
|View full text |Cite
|
Sign up to set email alerts
|

Properties and interactions of poly(vinyl alcohol)-sago pith waste biocomposites

Abstract: In this study, blending of poly (vinyl alcohol) (PVA) and sago pith waste (SPW) was prepared by a one-step melt extrusion. The physico-mechanical, Fourier transform-infrared (FT-IR), moisture sorption, rheological, and thermal characterization were conducted. Incorporation of PVA in SPW improved the tensile modulus, whereas the tensile strength reduced. The FT-IR analysis has shown that SPW could be introduced into the PVA network via the formation of hydrogen bonds between the PVA and SPW clusters. The intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The addition of toluene on poplar caused three bands including 3069 cm −1 for C-H stretching, 1497 cm −1 for C-C stretching, and 728 cm −1 for C-H out of plane bending [41]. Glycerol on poplar had the bands for O-H stretching at 3341 cm −1 , C-H stretching at 2948 and 2897 cm −1 , C-H deformation of secondary alcohol at 1333 and 1239 cm −1 , C-O stretching of primary alcohol at 1034 cm −1 , and O-H bending at 923 cm −1 [42,43]. Chloroform contaminants also showed at 1220 and 755 cm −1 for C-H bending and CCl 3 stretching [34].…”
Section: Commonly Used Pretreatment and Preprocessing Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of toluene on poplar caused three bands including 3069 cm −1 for C-H stretching, 1497 cm −1 for C-C stretching, and 728 cm −1 for C-H out of plane bending [41]. Glycerol on poplar had the bands for O-H stretching at 3341 cm −1 , C-H stretching at 2948 and 2897 cm −1 , C-H deformation of secondary alcohol at 1333 and 1239 cm −1 , C-O stretching of primary alcohol at 1034 cm −1 , and O-H bending at 923 cm −1 [42,43]. Chloroform contaminants also showed at 1220 and 755 cm −1 for C-H bending and CCl 3 stretching [34].…”
Section: Commonly Used Pretreatment and Preprocessing Solventsmentioning
confidence: 99%
“…FTIR band assignments of common biomass processing solvents on poplar[32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Cont.…”
mentioning
confidence: 99%
“…From the results obtained, it can be observed that the pure PVA films demonstrated lower percentage of water absorption than the PVA/starch films. This is due to the fact that PVA and starch is highly hydrophilic polymer in nature caused by the presence of many hydroxyl groups in it and thus capable of forming hydrogen bonds in water [10]. Water absorption occurs almost entirely in the amorphous region of a polymeric system [11].…”
Section: Mechanical Propertiesmentioning
confidence: 99%